2011
DOI: 10.1542/peds.2010-1307
|View full text |Cite
|
Sign up to set email alerts
|

Medical Home and Out-of-Pocket Medical Costs for Children With Special Health Care Needs

Abstract: Families with CSHCN incur lower out-of-pocket medical costs when their children receive health care in a setting in which the care-coordination component of the medical home is in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…15 By definition, a medical home provides care coordination and other important functionalities. 19 Lack of a medical home has been associated with increased risk of forgone or delayed care among children 20 and, for families of CSHCN, increased outof-pocket health-related costs 21 and fewer referrals to needed specialty care. 12 Conversely, rates of visits to specialists have been demonstrated to decrease among CSHCN in medical homes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 By definition, a medical home provides care coordination and other important functionalities. 19 Lack of a medical home has been associated with increased risk of forgone or delayed care among children 20 and, for families of CSHCN, increased outof-pocket health-related costs 21 and fewer referrals to needed specialty care. 12 Conversely, rates of visits to specialists have been demonstrated to decrease among CSHCN in medical homes.…”
Section: Discussionmentioning
confidence: 99%
“…However, consumer-based perception of quality and need of care are widely used measures of health care delivery. Although numerous publications define the medical home as we have done with the NS-CSHCN, 20,21,36,41,43,44 the items included to meet these criteria do not capture all activities of the medical home or care coordination (such as patient registries, team based care, comanagement arrangements with specialists, and other concepts of the patient-centered medical home). 45 However, the items used to define the constructs of the medical home and care coordination are aligned with the AAP definitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For children with ADHD, the PCMH model has been associated with better adherence to recommended medications, improved school performance and interpersonal relationships, and decreased adverse events. 13 Some studies have suggested that for CSHCN, generally, families may incur fewer out-ofpocket costs if care is provided by a PCMH that includes effective care coordination 14 and is linked with well-organized community-based systems. 15 A medical home could not only help them with care coordination but also provide specific support services from coaching for behavior management to facilitated prescription refills.…”
mentioning
confidence: 99%
“…Such studies have found the PCMH to be associated with increased utilization of primary care services 13 and decreased emergency care encounters, 14,15 family burden, 16 and out-of-pocket expenses. 17 …”
mentioning
confidence: 99%